Surgical factors that contribute to tibial periprosthetic fracture after cementless Oxford Unicompartmental Knee Replacement: a finite element analysis - Min, Xiaoyi; Marks, Laurence; Mellon, Stephen; Hiranaka, Takafumi; Murray, David (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundTibial periprosthetic fracture (TPF) is a severe complication of cementless Oxford Unicompartmental Knee Replacement (OUKR) with patient risk factors including small tibial size and tibia vara with an overhanging medial tibial condyle. Surgical factors also influence fracture but remain poorly defined. This finite element (FE) analysis study identified surgical risk factors for TPF after OUKR and determined the optimal tibial component positioning to minimise fracture risk.MethodsKnees in two very high-risk, small, bilateral OUKR patients who had a TPF in one knee and a good result in the other were studied with FE analysis. Each patient’s unfractured tibia was used as a comparator to study surgical factors. The tibial geometries were segmented from the pre-operative CT scans and FE models were built with the tibial components implanted in their post-operative positions. The resections in the fractured and unfractured tibias were compared regarding their mediolateral position, distal-proximal position, internal-external rotation and varus-valgus orientation. Models of the TPF tibial resections in the contralateral sides were also built in both patients. The risk of TPF was assessed by examining the magnitude and location of the highest maximum principal stress.ResultsIn both patients, large differences were found in the position and orientation of the tibial components in the fractured and unfractured tibias with the components in the fractured tibias placed more medially and distally. Suboptimal saw cuts resulted in poor positioning of the tibial components and created very high local stresses in the bone, particularly anteriorly (157 MPa and 702 MPa in the fractured side vs. 49 MPa and 63 MPa in the unfractured side in patient 1 and 2 respectively), causing fractures.ConclusionIn small patients with marked tibia vara the surgery is unforgiving. To avoid fracture, the horizontal cut should be conservative, aiming for a 3 bearing, the vertical cut should abut the apex of the medial tibial spine, and extreme internal or external rotation should be avoided. The component should be aligned with the posterior cortex and should not overhang anteriorly. In addition, contrary to current recommendations, the tibial component should be placed in varus (about 5°).